The Effects of Wages and Welfare Facilities on Employee Productivity: Mediating Role of Employee Work Motivation - Mohammad Nurul Alam; Md Mahmudul Hassan; Dorothea Bowyer; Md Reaz (Australasian Accounting, Business and Finance Journal, 2020)
Purpose- Garment employee productivity in Bangladesh is the lowest compared to its competitors such as China, India, Pakistan and Sri Lanka. The Bangladeshi Ready-Made Garment (RMG) industry will find it a challenge to survive in the global market unless they improve employee productivity. Therefore, the primary purpose of this study was to observe the relationship among wages and benefits, welfare facilities, employee work motivation and employee productivity. Design/Methodology/Approach- The study was conducted under the positivism philosophy for which Maslow’s Hierarchy of Needs Theory was used for framing the hypotheses. A deductive approach, explanatory research design and a quantitative methodology was followed in order to conduct the study. Through a questionnaire survey, twenty-five items were taken from existing literature to measure the variables. By a systematic probability sampling technique, 500 samples were collected from the target population. Thereafter, SPSS and SEM using Smart-PLS were utilised for analysing and developing the model. Findings- The outcome of the analysis revealed that all seven hypotheses were supported. Practical Implications- These findings will assist the policymakers, the government of Bangladesh, factory owners, managers and other stakeholders to formulate new policies and practices. Originality/Value- This study explores the relationship among wages and benefits, welfare facilities, employee work motivation and employee productivity which has not been explored theoretically and tested empirically in a Bangladeshi context. In the future, comparative research can be carried out by collecting samples from the EPZ (Export Processing Zone) and non-EPZ factories.
Keywords: Employee work motivation; wages and benefits; welfare facilities; employee productivity; readymade garment industry; Bangladesh